2001
DOI: 10.1083/jcb.200106147
|View full text |Cite
|
Sign up to set email alerts
|

A regulatory cascade involving retinoic acid, Cbfa1, and matrix metalloproteinases is coupled to the development of a process of perichondrial invasion and osteogenic differentiation during bone formation

Abstract: Tissue-remodeling processes are largely mediated by members of the matrix metalloproteinase (MMP) family of endopeptidases whose expression is strictly controlled both spatially and temporally. In this article, we have examined the molecular mechanisms that could contribute to modulate the expression of MMPs like collagenase-3 and MT1-MMP during bone formation. We have found that all-trans retinoic acid (RA), which usually downregulates MMPs, strongly induces collagenase-3 expression in cultures of embryonic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
63
0

Year Published

2003
2003
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(69 citation statements)
references
References 57 publications
6
63
0
Order By: Relevance
“…MMP-13 has a particular affinity for type II collagen and selectively enhances cleavage and denaturation of this type of collagen (43), and can also cleave aggrecan at specific sites (44). Interestingly, recent studies have also shown that retinoid-related signals strongly enhance the induction of MMP-13 in chondrocytic cells through the action of RAR-RXR heterodimers (45). In addition, reduced expression of MMP-13 is observed in cytokine-stimulated cells when NF-B is maintained in the cytoplasm by constitutive levels of I B (46).…”
Section: Discussionmentioning
confidence: 99%
“…MMP-13 has a particular affinity for type II collagen and selectively enhances cleavage and denaturation of this type of collagen (43), and can also cleave aggrecan at specific sites (44). Interestingly, recent studies have also shown that retinoid-related signals strongly enhance the induction of MMP-13 in chondrocytic cells through the action of RAR-RXR heterodimers (45). In addition, reduced expression of MMP-13 is observed in cytokine-stimulated cells when NF-B is maintained in the cytoplasm by constitutive levels of I B (46).…”
Section: Discussionmentioning
confidence: 99%
“…Because the expression of MMP-13 is elevated in the arthritic joints (35,39), this proteinase is thought to be a key enzyme associated with osteoarthritis. Recent studies have shown that retinoid-related signals strongly enhance the induction of MMP-13 in chondrocytic cells through the action of retinoic acid receptor-retinoid X receptor heterodimers (41). In addition, it has been demonstrated that MMP-13 induction by inflammatory cytokines requires the activation of NFB (42).…”
mentioning
confidence: 99%
“…To directly probe TG2 functions in chondrocyte differentiation and calcification we have taken advantage of the recent generation of TG2 knockout mice, which are phenotypically normal (23,24). To specifically assess for direct TG2 involvement in articular chondrocyte hypertrophy, we studied the effects on primary chondrocytes of CNP (25) and of the vitamin A-derived metabolite all-trans retinoic acid (ATRA) (26,27). CNP is expressed in developing long bones, and the stimulatory effects of CNP on chondrocyte proliferation and hypertrophy are essential for normal growth plate development (25).…”
mentioning
confidence: 99%
“…CNP is expressed in developing long bones, and the stimulatory effects of CNP on chondrocyte proliferation and hypertrophy are essential for normal growth plate development (25). ATRA promotes maturation to hypertrophy and calcification by chick sternal chondrocytes in vitro (26) in a manner that requires the transcription factor Cbfa1 (27). In addition, hypervitaminosis A and toxicity of certain other retinoids is associated with accelerated terminal differentiation of endochondral chondrocytes and premature epiphyseal closure in vivo (28,29).…”
mentioning
confidence: 99%